TEST PERFORMANCE OF FORAGE CHOPPER VERTIKAL WONOSARI TYPE I - Fadli, Ihwan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
This research aimed at testing performance of forage chopper verticalWonosari type I by observation coveringuniformity, capacity ofmachinework, and consumptionfuel. Research located inSumberrejo village, subdistrictof Batanghari, district of Lampung Timur which began in months Juny – Agustus 2014. Themethod usedwas aCompletely Randomized Design (CRD) with two factorial. The first factor is the three engine speeds with levels(800, 1400 and 1800 rpm), while the second factor is combined of feed freshness (fresh, withered a day andwithered twodays). Every treatmentwere repeated three times so the total thereare 27 treatment. Parameter thatwas statistically tested is uniformity of 2 – 5 cmchopped size then continued by F test, LSD 5%and 1%. The resultsshow that the chopped size 2 – 5 cm most be obtained at the speed 1400 rpmfor fresh corn stalks and withereda daywith the 32.19%and 39.69%percentage,while thewithered corn stalks two days using the speed 1800 rpmwith 30.12% percentage. The results of analysis of variance calculation shows that the uniformity of choppedsize 2 – 5 cm was different. The work capacity of themachine at speed of 1400 rpm was 834 kg/hour with the2.17 liters/hour consumption fuel.Keywords:Capacity, Chopper,Chopped size,Fuel consumption,The performance test